Pengaruh Fitur Virtual Try-On, Online Customer Review, dan Persepsi Harga Terhadap Keputusan Pembelian Kosmetik Pada Aplikasi Shopee - Viohafeni, Zalma Dwi; Aliyah, Kisti Nur (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
This research aims to prove the influence of virtual try-on, online customer reviews, and price perceptions on purchasing decisions for Madame Gie products in the Shopee application. The population in this study are consumers in the city of Surakarta. The research sample used is consumers who have purchased Madame Gie products. This research method is a quantitative research with non-probability sampling technique using purposive sampling method. The research data was obtained by 100 respondents and processed using multiple linear regression analysis techniques using IBM SPSS Statistics software version 23. The results showed that Virtual Try-On had a positive and significant effect on Purchase Decisions, Online Customer Review had a positive and significant effect on Decisions Purchases, and Price Perceptions have a positive and significant effect on Purchase Decisions.